Approche expérimentale de la navigation précolombienne dans les Antilles - Benoît Bérard; Jean-Yves Billard; Thierry L’Etang; Guillaume Lalubie; Costantino Nicolizas; Bruno Ramstein; Emma Slayton (Journal de la Société des Américanistes)
Understanding the navigation capacities of the Eastern Caribbean pre-Columbian population is crucial for the community working in the Antilles. We have chosen to focus our work on an experimental approach of these techniques. Our ambition was to set up an experimental program including all the aspects associated with the building and the utilization of the kanawa. Thus, we have conducted an ethno-archaeological study of the kanawa building process followed by the Kali’ña from French Guyana. Then, the « Akayouman » kanawa was made into a 3D model to support a hydrostatic analyse. Finally, the heart of the project was composed of gathering and studying the data collected during our expeditions in the kanawa.